Fostering a Generation of Sustainability Awareness: Strategies for Basic Education Based on a Systematic Literature Review - Dewi Ramadany, Lisa; Sujana, Atep; Andi Hidayat, Febrian (International Conference on Elementary Education, 2025)
The increasing global environmental challenges highlight the urgent need to foster sustainability awareness from an early age. Elementary education serves as a critical phase for instilling values and attitudes that shape lifelong sustainable behaviors. This systematic literature review analyzes effective educational strategies for enhancing sustainability awareness among elementary school students. Guided by PRISMA 2020 protocols, a comprehensive search was conducted across Scopus, Dimensions, and Garuda databases, focusing on articles published between 2019 and 2024. Through a rigorous selection process, 25 studies were identified, offering insights into successful interventions. Findings categorize these strategies into three key approaches: experiential and project-based learning, curriculum integration, and digital interactive tools. Experiential learning engages students in hands-on activities, fostering emotional connections to environmental issues. Curriculum integration, particularly in science and social studies, enhances students’ holistic understanding of sustainability. Meanwhile, digital tools such as educational games and simulations boost engagement and accessibility, though challenges related to technological infrastructure and teacher readiness remain. The review concludes that a multi-faceted approach combining experiential, curricular, and digital strategies offers the greatest potential for cultivating sustainability awareness. By implementing these integrated and context-specific strategies, educators and policymakers can design impactful and sustainable environmental education programs that prepare the next generation to address global environmental challenges..